STUDY OF THE EFFECT OF SOIL CEMENT ELEMENTS WHEN STABILIZING ROADBED MODEL IN LABORATORY CONDITIONS - Petrenko, V. D; Tiutkin, O. L.; Sviatko, I. O. (Science and Transport Progress, 2017)
Purpose.Experimental studies allow determining th estress-strain state or bearing capacity of the tested soil body. A preliminary study of the results of model testing and experimental research allows us to find the optimal solutions and to justify the parameters of the chosen technology. The purpose of this work is to determine the effect of soil cement elements when stabilizing the roadbed on a weak subgrade using the soil tests in laboratory conditions. Methodology. During the development of measures for the reconstruction and consolidation of soil bodies, their strength is tested using many methods. In all cases, we take into account the physical and mechanical characteristics of soils obtained as a result of research, as well as the existing regulatory documents. We performed the experimental studies by model testing in laboratory conditions. The model testing was based on the corresponding relationships between geometric sizes, mechanical properties of materials, loads and other factors on which the stress-strain state depends. During testing, the model was loaded gradually. We maintained each load level up to conditional stabilization of the soil deformation. We took the readings from measuring devices at each stage of loading after achievement of stabilization of soil mass deformations. We fixed the readings in the test journal. Findings. During stabilization with soil cement piles there is an improvement in mechanical properties, which leads to a decrease in deformations by 2…3.5 times. Each test is accompanied with graphs of relative deformations-stress dependence, as well as deformation curves and compression curves. According to the results of experimental stu-dies, it can be seen that when testing a model with cement piles, compared with a model without soil cement piles, the relative deformations of the samples taken prior to the experiment and after the experiment almost coincide, indicating a decrease in deformability under load. Originality. We proved that this stabilization type positively affects the stress-strain state of the soil body, by increasing its physical and mechanical characteristics. The obtained results allow for rational design of subgrade stabilization work with the help of modern technologies.Practicalvalue. The in-depth analysis of the results of experimental studies opens up possibilities for theoretical synthesis and development of theoretical foundations, which will allow in the future avoiding, in the similar cases, the experimental verification of the stabilization type given for the relative type of soil. It is confirmed that this method of stabilization used can be applied in real conditions.